Experience of excess heavy metal content in drinking water for human organizm - Архіпова, Г.І.; Мудрак, Т.О.; Завертана, Д.В. (Proceedings of National Aviation University, 2010)
Heavy metals are toxic to a widespread of pollutants. Heavy metals are widely used in various industrial enterprises, and, despite the penetrating clearing actions, compounds of heavy metals in industrial waste water. A considerable number of these compounds into the water through the atmosphere. The environmental risk of heavy metals is that they are actively absorbed by phytoplankton and then transferred to humans by food chain. Into two groups of metals, different in their ecological significance. The first group of elements, maximum allowable concentration (MAC) are close to their background values in natural water. This, for example, iron, manganese, strontium. The second group includes metals (copper, lead, zinc), which far exceed the MCL real natural background values. For the normal functioning of the human body requires to achieve a balanced exchange of microelements, the violation of which leads to serious diseases and poisonings.